A Systematic Review of Trans Fat Reduction Initiatives in the Eastern Mediterranean Region - Al-Jawaldeh, Ayoub; Taktouk, Mandy; Chatila, Aya; Naalbandian, Sally; Abdollahi, Zahra; Ajlan, Buthaina; Al Hamad, Nawal; Alkhalaf, Majid M.; Almamary, Salima; Alobaid, Rawan; Alyafei, Salah Abdulla; Azizi, Mohammad Hosein; et al. (Frontiers in Nutrition, 2021)
High intakes of trans fatty acids (TFA), particularly industrially-produced TFA, are implicated in the etiology of cardiovascular diseases, which represent the leading cause of mortality in the Eastern Mediterranean Region (EMR). This systematic review aims to document existing national TFA reduction strategies in the EMR, providing an overview of initiatives that are implemented by countries of the region, and tracking progress toward the elimination of industrially-produced TFA. A systematic review of published and gray literature was conducted using a predefined search strategy. A total of 136 peer-reviewed articles, gray literature documents, websites and references from country contacts were obtained, up until 2 August 2021. Randomized-control trials, case-control studies, and studies targeting unhealthy population groups were excluded. Only articles published after 1995, in English, Arabic or French, were included. Key characteristics of strategies were extracted and classified according to a pre-developed framework, which includes TFA intake assessment; determination of TFA levels in foods; strategic approach; implementation strategies (TFA bans/limits; consumer education, labeling, interventions in public institution settings, taxation), as well as monitoring and evaluation of program impact. Thirteen out of the 22 countries of the EMR (59%) have estimated TFA intake levels, 9 have determined TFA levels in foods (41%), and 14 (63.6%) have national TFA reduction initiatives. These initiatives were mainly led by governments, or by national multi-sectoral committees. The most common TFA reduction initiatives were based on TFA limits or bans (14/14 countries), with a mandatory approach being adopted by 8 countries (Bahrain, Iran, Jordan, KSA, Kuwait, Morocco, Oman and Palestine). Complementary approaches were implemented in several countries, including consumer education (10/14), food labeling (9/14) and interventions in specific settings (7/14). Monitoring activities were conducted by few countries (5/14), and impact evaluations were identified in only Iran and the UAE. The robustness of the studies, in terms of methodology and quality of assessment, as well as the lack of sufficient data in the EMR, remain a limitation that needs to be highlighted. Further action is needed to initiate TFA reduction programs in countries that are lagging behind, and to ensure rigorous implementation and evaluation of ongoing programs.